Expansion of a Subset Within the C2 Subclade of Escherichia coli Sequence Type 131 (ST131) Is Driving the Increasing Rates of Aminoglycoside Resistance. (8th September 2020) - Hojabri, Zoya; Darabi, Narges; Mirmohammadkhani, Majid; Rahimi, Hamzeh; Hemmati, Romina; Saeedi, Zahra; Roustaee, Kiarash; Leekitcharoenphon, Pimlapas; Pajand, Omid; Aarestrup, Frank M
Abstract: Background: Sequence type 131 (ST131) of Escherichia coli is a pandemic clone that drives the increasing rates of antibiotic resistance. While the pervasiveness of ST131 clade C, especially subclades C2 and C1-M27, has been demonstrated in numerous global surveys, no report about the ST131 clades and their virotypes has been published from Iran so far. Methods: A collection of 73 consecutive ST131 isolates from extraintestinal specimens was investigated for determination of virotypes, antibiotic susceptibility patterns, resistance/virulence determinants, and clade subsets. Results: Most of the isolates belonged to subclade C2 (33/73; 45.2%), which had the highest virulence factor (VF) scores and resistance rates, followed by C1-M27 (18; 24.6%), C1-non-M27 (14; 19.1%), and A (8; 10.9%). The distinctive profiles of subclade C2 virulence genes were revealed by principle coordinates analysis testing. The distribution of the hlyA virulence gene among subclade C2 was not uniform, so that positive strains (21; 63.6%) showed significantly higher rates of resistance ( bla CTX-M-15, bla OXA-1, aac(6')-Ib-cr, aac(6')-Ib, aac(3)-IIa ) and virulence ( hra, tia/hek, K5, cnf, papGII, papC ) markers and gentamicin/tobramycin resistance. Virotype C as the most common virotype (34; 46.5%) was predominant among the subclade C1 population, while virotypes E and F (21; 28.7%) were detected among subclade C2, which had the highest VF scores and aminoglycoside resistance rates. Conclusions: The appearance of virotypes E and F among subclade C2 strains with higher rates of aminoglycoside resistance/virulence gene content shows the shifting dynamics of this pandemic clone in response to antibiotic selection pressure by establishing subsets with higher survival potential.